Linguistic and non-linguistic barriers to English speaking ability among Saudi EFL learners - Dawood A. Mahdi (Journal of Pedagogical Research, 2024)
The study aims to assess the role of linguistic and non-linguistic barriers on the English-speaking abilities of Saudi EFL learners. A cross-sectional design was adopted and convenience sampling was employed to recruit the EFL learners in Saudi Universities. An online survey was conducted. Descriptive statistics, t-tests, and factor analysis were performed. The results of the study showed that non-linguistic barriers, affecting English-speaking capabilities included fear of making mistakes, shyness, anxiety, confidence, and a lack of interest. Where the most significant factor was confidence in to impact of English speaking. Moreover, among linguistic barriers i.e., grammar, vocabulary, and pronunciation, vocabulary was the most significant factor to influence the English-speaking ability of the Saudi EFL students. However, no gender-wise discrepancies were found in experiencing these barriers. The study concluded that there was no significant difference between male and female learners. Both genders faced linguistic and non-linguistic barriers. However, pronunciation errors, a lack of vocabulary, and poor knowledge about grammatical structure were the linguistic barriers, faced by the students.